Geoid modelling in the area of Fagnano Lake, Tierra del Fuego (Argentina): Insights from mean lake-level observations and reduced gravity data - Gomez, Maria Eugenia (2013)
This paper evaluates a combined geoid model in the area of Fagnano Lake located in Tierra del Fuego, Argentina. The model includes GPS/levelling points, gravity data and GPS buoy observations on the lake. The GPS buoy information allowed to determine a mean lake level (MLL) surface which was used to extend the geoid model to an area with restricted access by land (Del Cogliano et al. 2007). An approach to optimize the selection and distribution of the MLL data is developed in order to use them as input in the Equivalent Source Technique, and to combine them with different types of observations. Furthermore, the global geopotential model EGM2008 is validated in the remote lake area. This model does not include observed gravity data in this region. Its behaviour is compared to the results of our observations along the levelling lines. Differences of several decimetres are found when EGM2008 geoid undulations are compared to geoid undulations derived from observations in this region. In the areas where EGM2008 relies on real gravimetric observations, differences between model and observations are only of a few centimetres. The comparison of the EGM2008 model with our observations reveals the effect of missing or not representative gravity information may have on the estimation of geoid undulations in high mountain regions. The data on which EGM2008 is based in the Fagnano Lake area does not result from gravimetric observations on land. Therefore, we consider them as not representative and we show that their effect can be significant in such areas.